Peran Baznas dalam Mensejahterakan Ekonomi Masyarakat Kota Medan - Farhan Edma Manurung; Muhammad Ikhsan Harahap (Universitas Muhammadiyah Enrekang, 2022)
Zakat is included in worship in the field of property which has a very important position in building society. If zakat is managed properly, its collection and distribution will certainly be able to raise the welfare of the community. Carrying out the obligation to pay zakat is also believed to be used as an alternative to alleviating poverty in the community. Zakat funds can contribute more and more broadly and touch all aspects of life, if the distribution can be directed to productive activities such as community empowerment. The research method used in this study is a qualitative descriptive method that describes the conditions and phenomena in the field. The type of data used in this research is primary data. This research was conducted at the National Amil Zakat Agency of North Sumatra Province Jalan Haji Hospital No.47, Medan Estate, Kec. Percut Sei Tuan, Deli Serdang Regency, North Sumatra-20371 for one full month. The result of this research is the utilization of productive zakat funds carried out by the North Sumatra Baznas, namely the system for utilizing productive zakat in the welfare of mustahik that is carried out by Baznas is correct. This can be seen how the achievements obtained in this work program, so as to provide positive results to be a way out and improve the economy of Muslims and have an impact on mustahik to be able to fulfill their lives with the business they live from the results of the productive zakat empowerment.